WHO/ILO work-related burden of disease and injury: Protocol for systematic reviews of occupational exposure to dusts and/or fibres and of the effect of occupational exposure to dusts and/or fibres on pneumoconiosis. (October 2018) - Mandrioli, Daniele; Schlünssen, Vivi; Ádám, Balázs; Cohen, Robert A.; Colosio, Claudio; Chen, Weihong; Fischer, Axel; Godderis, Lode; Göen, Thomas; Ivanov, Ivan D.; Leppink, Nancy; Mandic-Rajcevic, Stefan; et al.
Abstract: Background: The World Health Organization (WHO) and the International Labour Organization (ILO) are developing a joint methodology for estimating the national and global work-related burden of disease and injury (WHO/ILO joint methodology), with contributions from a large network of experts. In this paper, we present the protocol for two systematic reviews of parameters for estimating the number of deaths and disability-adjusted life years attributable to pneumoconiosis from occupational exposure to dusts and/or fibres, to inform the development of the WHO/ILO joint methodology. Objectives: We aim to systematically review studies on occupational exposure to dusts and/or fibres (Systematic Review 1) and systematically review and meta-analyse estimates of the effect of occupational exposure to dusts and/or fibres on pneumoconiosis (Systematic Review 2), applying the Navigation Guide systematic review methodology as an organizing framework. Data sources: Separately for Systematic Reviews 1 and 2, we will search electronic academic databases for potentially relevant records from published and unpublished studies, including Medline, EMBASE, Web of Science and CISDOC. We will also search electronic grey literature databases, Internet search engines and organizational websites; hand-search reference list of previous systematic reviews and included study records; and consult additional experts. Study eligibility and criteria: We will include working-age (≥15 years) study participants in the formal and informal economy in any WHO and/or ILO Member State but exclude children (<15 years) and unpaid domestic workers. Eligible risk factors will be dusts and/or fibres from: (i) asbestos; (ii) silica; and/or (iii) coal (defined as pure coal dust and/or dust from coal mining). Included outcomes will be (i) asbestosis; (ii) silicosis; (iii) coal worker pneumoconiosis; and (iv) unspecified pneumoconiosis. For Systematic Review 1, we will include quantitative prevalence studies of occupational exposure to dusts and/or fibres (i.e. no versus any exposure) stratified by country, sex, age and industrial sector or occupation. For Systematic Review 2, we will include randomized controlled trials, cohort studies, case-control studies and other non-randomized intervention studies with an estimate of any occupational exposure to dusts and/or fibres on the prevalence of, incidence of or mortality due to pneumoconiosis, compared with the theoretical minimum risk exposure level of no exposure. Study appraisal and synthesis methods: At least two review authors will independently screen titles and abstracts against the eligibility criteria at a first stage and full texts of potentially eligible records at a second stage, followed by extraction of data from qualifying studies. At least two review authors will assess risk of bias and the quality of evidence, using the most suited tools currently available. For Systematic Review 2, if feasible, we will combine relative risks using meta-analysis. We will report results using the guidelines for accurate and transparent health estimates reporting (GATHER) for Systematic Review 1 and the preferred reporting items for systematic reviews and meta-analyses guidelines (PRISMA) for Systematic Review 2. PROSPERO registration number: CRD42018084131. Highlights: A protocol was prepared for two systematic reviews in the field of occupational health. Principles of the Navigation Guide systematic review methodology were applied. The protocol detailed instructions how to assess the quality of selected studies.